PERLINDUNGAN HUKUM TERHADAP ANDIKPAS (ANAK DIDIK PEMASYARAKATAN) DI LPKA KELAS I PALEMBANG - M Faisal Alnanditya (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2021)
This article aims to describe the nature of children, the protection of children's laws, and the rights of children during the criminal period IN LPKA. This article is also the result of research on the fulfillment of children's rights at LPKA class I Palembang. Although the child is undergoing a criminal in LPKA but the child must be legally protected by knowing what rights they have found during the criminal procedure at LPKA. The legal protection system for children at LPKA contained in LAW No. 11 Th. 2012 on SPPA, LAW No. 12 Th. 1995 on Correctional LAW No. 35 Th. 2014 on child protection. This research is a qualitative study with the type of field research whose main data source is taken from objects directly in the research area. And using a yuridist empirical approach method. After knowing what rights will be found AndikPas (students of correctional) then the implementation to exercise those rights. There are also rights that have not been met because of problems or ba